2023
DOI: 10.1177/10668969231171941
|View full text |Cite
|
Sign up to set email alerts
|

Undifferentiated Carcinoma of Esophagus with SMARCA4 Deletion Expressing Synaptophysin: A Potential Diagnostic Pitfall

Abstract: Undifferentiated carcinoma of the esophagus is an entity that is included in WHO classification of digestive systems fifth edition (2018). The definition of this entity is a malignant esophageal epithelial tumor that lacks definite microscopic features of squamous, glandular, or neuroendocrine differentiation. It is a challenging diagnosis to make due to lack of diagnostic criteria. We report a case from a 45 years old man with a mass in the lower third of esophagus. Biopsy showed an epitheloid neoplasm with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Table 2 lists the nine publications and summarizes the patient characteristics, clinical presentation, associated risk factors, treatment, and follow-up information. Notably, one case reported in the study by Cui et al ( 25 ) was previously documented in a separate case report ( 26 ); therefore, these two publications were summarized together. Similarly, one case reported in the study by Gupta et al ( 28 ) was previously documented in a standalone case report ( 23 ); consequently, the results of these two publications were consolidated into a singular summary.…”
Section: Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Table 2 lists the nine publications and summarizes the patient characteristics, clinical presentation, associated risk factors, treatment, and follow-up information. Notably, one case reported in the study by Cui et al ( 25 ) was previously documented in a separate case report ( 26 ); therefore, these two publications were summarized together. Similarly, one case reported in the study by Gupta et al ( 28 ) was previously documented in a standalone case report ( 23 ); consequently, the results of these two publications were consolidated into a singular summary.…”
Section: Search Resultsmentioning
confidence: 99%
“…Similarly, Gupta et al reported that three out of five tumors were from the distal esophagus, one from the GEJ, and one from the mid to distal esophagus ( 28 ). All four patients from the series reported by Cui et al had a tumor from the distal esophagus ( 25 , 26 ), whereas all four patients reported by Chang et al had a tumor from the GEJ ( 30 ). The tumors detected on EGD varied in size, ranging from 2.5 to 10.0 cm ( 25 , 26 , 28 - 30 ).…”
Section: Clinical Features and Associated Risk Factors ( ...mentioning
confidence: 90%
See 3 more Smart Citations